Situs Inversus Totalis with Hydrocephalus in an Adult: A Rare Case Report - Roka, Yam Bahadur; Karki, Mohan; Thapa, Ashish Jung; Roka, Narayani (Nepal Journal of Neuroscience, 2019)
Situs in versus is a rare anomaly where there is reversal of the visceral organ location and usually associated with Kartagener syndrome and digestive, circulatory and respiratory diseases abnormalities. The lateralization of visceralorgans to a side is a feature of vertebrates and humans are externally symmetrical but internally asymmetrical. Normal anatomy imparts the heart to left and the liver to the right which is found not only in humans but also other animals. This case showed aqueduct stenos is with hydrocephalus with normal corpus callosum. The association of situs in versus with ciliary abnormalities and therefore is rarely associated with hydrocephalus, polycystic disease or retinal degeneration. PubMed search for situs in versus total is with hydrocephalus showed only 7 results with 3 of them in animal studies, one was not relevant and the rest in human. Hydrocephalus was present in only two studies, one of them cadaveric finding. The association with hydrocephalus is very rare and we present such a case report.